Paleocene–Eocene palynomorphs from the Chicxulub impact crater, Mexico. Part 2: angiosperm pollen. (2nd July 2020) - Smith, Vann; Warny, Sophie; Jarzen, David M.; Demchuk, Thomas; Vajda, Vivi; Gulick, Sean P.S.
Abstract: At the end of the Cretaceous Period, an asteroid collided with the Earth and formed the Chicxulub impact structure on the Yucatán Platform. International Ocean Discovery Program (IODP) Expedition 364 drilled into the peak ring of the Chicxulub impact crater. The post-impact section of the core was sampled for terrestrial palynological analysis, yielding a high-resolution record ranging from the early Paleocene to the earliest Eocene (Ypresian), including a black shale deposited during the Paleocene–Eocene Thermal Maximum (PETM). The IODP 364 core provides the first record of floral recovery following the K–Pg mass extinction from inside the Chicxulub impact crater. The systematic taxonomy of the angiosperm pollen provided here follows a separate publication describing the systematic paleontology of the plant spores and gymnosperm pollen from the IODP 364 core (Smith et al. 2019 ). The Paleocene section of the core is nearly barren, but with unusually high relative abundances of the angiosperm pollen Chenopodipollis sp. A (comparable to the Amaranthaceae), possibly indicating an estuarine pollen source. Pollen recovery is higher in the PETM section, and variable but generally increasing in the later Ypresian section, with excellent preservation in several samples. Estimated absolute ages of several potentially useful regional biostratigraphic events are provided. One new genus ( Scabrastephanoporites ) and five new species ( Brosipollis reticulatus, Echimonocolpites chicxulubensis, Psilastephanocolporites hammenii, Scabrastephanoporites variabilis, and Striatopollis grahamii ) are formally described.